Urgensi Pertemuan dan Presentasi Dalam Organisasi Bisnis - Gita Islya Asmara; Nita Erdina; Rizki Ananda Ariza; Suhairi Suhairi (Da'watuna: Journal of Communication and Islamic Broadcasting, 2021)
The purpose of this article is to identify how to important it is to implement meeting and presentation management in improving quality and effectiveness in business organization. In the business world, there two important things in a running a business. First, a meeting or a meeting where is more of an activity that becomes a means for exchanging data and information, a place to dialogue ideas and concepts, and a place for the exchange of ideas through productive discussions. Any business organization will need fresh and creative new ideas and important information exchange. Second, in every meeting or meeting requires the delivery of information or a good presentation in general, the presentation is done to persuade, inform, motivate or inspire other. Presentations and meetings is an important thing that must be prepared if you are in the business world. The success or failure of a business is influenced by the way we prepare meetings and presentations. So, don’t ever underestimate the issue of this meetings and presentations because this is where all members of business organization in the discussion voice their opinion and ideas. Therefore, it is important for the author to convey two things that are very meaningful in the business world to be developed in you.